Mining Law and Economic Policy Critical Perspectives and Challenges for Mining in Africa - Debrah, Akua.; Mtegha, Hudson (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the impacts of current mining licensing regimes in Africa and how they influence sustainable development principles. International law and conventions on mining are used as a lens to examine a regionalized perspective of the history of mining law and customary land law. Alternative approaches are then suggested, through a comparative and sovereignty-based study of mining laws and policies, to see how the challenge of uneven development can be combatted using minerals. This book aims to highlight how mineral possessions can transform communities if the economic policies, customary law structures, and the geopolitical landscape guarantee inclusivity and equal partnerships. It will be relevant to researchers and policymakers interested in mineral economics, mining law, and African economies. Akua Debrah is a Visiting Lecturer at the Wits Mining Institute, University of the Witwatersrand. Hudson Mtegha is a Visiting Adjunct Professor at the School of Mining Engineering, University of the Witwatersrand.
Chapter 1: Introduction -- PART I: Mining Laws and Policies in Selected African Countries -- Chapter 2: Democratic Republic of Congo -- Chapter 3: Ghana -- Chapter 4: Mozambique -- Chapter 5: South Africa I -- Chapter 6: South Africa II -- Chapter 7: South Africa III -- PART II: Regional Approaches to Mining, Sustainable Development and Permanent Sovereignty over Natural Resources -- Chapter 8: Regional Perspectives and the Africa Mining -- Chapter 9: Conclusions.
Keywords: Law and economics; Power resources; Environmental economics; Africa-Economic conditions; Industries; Property; Common law; Law and Economics; Resource and Environmental Economics; African Economics; Sector and Industry Studies; Common Property and Land Law